Purification and characteristion of type pullulanase from anoxybacillus species - Soh, Kar Yan, 1990-, author; Goh, Kian Mau, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - - Universiti Terknologi Malaysia, 2014